Developing and Validating Critical-Heutagogy Learning (CHL) to Enhance Lifelong Learning: A Rasch Analysis Approach - Kholid, Idham; Supriyadi, Supriyadi (Universitas Islam Negeri Raden Intan Lampung, 2023)
This research is dedicated to the development and validation of Critical-Heutagogy Learning (CHL), an innovative pedagogical approach designed to foster lifelong learning among university students. In an era characterized by rapid changes, the imperative for lifelong learning is paramount, necessitating individuals to continually update their knowledge and skills to remain adaptable and successful in diverse environments. To evaluate the validity and reliability of CHL, this study employs Rasch analysis. The development phase of CHL encompassed an exhaustive review of relevant literature, consultations with subject matter experts, and an iterative design methodology. This process was critical to ensure that CHL adhered to established principles of lifelong learning while promoting critical thinking and heutagogical practices. For the validation phase, CHL tools were administered to a heterogeneous group of students across multiple educational contexts. The gathered data underwent rigorous Rasch analysis to ascertain the framework's reliability, evaluate item fit, and pinpoint areas necessitating enhancements. The findings indicate that CHL is both a valid and reliable approach, with a high percentage (89.5%) of student respondents affirming its effectiveness in fostering engagement in learning and enhancing autonomous learning competencies. Additionally, this study delves into the interactions between bias and differential item functioning. The outcomes of this research offer a valuable contribution to the field of education, presenting a rigorously validated framework that supports lifelong learning. This is achieved through the promotion of critical thinking and the facilitation of independent learning skills, thus aligning with contemporary educational objectives and needs.